Experimental Study on the Reaction Conditions of a Methanol Steam Reforming Process. (May 2017) - Chiu, Yu-Jen; Chiu, Han-Chieh; Hsieh, Ren-Horn; Jang, Jer-Huan; Syu, Guo-Jhen
Abstract: The effects of various reaction conditions on a methanol steam reforming (MSR) process were analyzed in this paper by adopting design of experiment (DOE) techniques. The control factors considered are the length and the temperature of the catalyst bed, the steam-to-carbon ratio and the space velocity of the feedstocks, and the catalyst loading within the MSR reactor. The performance indices (quality characteristics) to be analyzed are the methanol conversion, the hydrogen production rate, the CO concentration in the produced mixture, and the ratios of the hydrogen production rate to the methanol feed rate and the catalyst loading, respectively. The major objective of the study is to analyze the holistic influences and the individual significance of the aforementioned reaction conditions on the defined MSR performance indices. Results suggest that temperature is the most significant factor that positively correlates the defined performance indices. The performance of a MSR reactor can be enhanced by raising the reacting temperature. Nonetheless, the CO concentration in the produced mixture is also increased. According to the present work, the effects of the reaction conditions on a MSR process can be analyzed simultaneously meanwhile the optimal combination of the concerned control factors can be obtained.